CHANGES IN HEALTH CARE UTILIZATION FOR LOW-SES ADULTS NEAR RETIREMENT AFTER THE ACA MEDICAID EXPANSION. (8th November 2019) - Tipirneni, Renuka; Langa, Kenneth M; McCammon, Ryan J; Zivin, Kara; Luster, Jamie; Ayanian, John Z
Abstract: Low-SES Americans approaching retirement are experiencing rising morbidity and mortality. We examined longitudinal changes in health care access, utilization, and health for low-SES adults age 55-64 before (2010-2012) and after (2014-2016) ACA Medicaid expansion using the HRS. With a longitudinal difference-in-differences (DID) approach adjusting for demographics and the complex survey design, we found that low-SES adults age 55-64 had increased rates of Medicaid coverage (+10.7 percentage points [pp] in expansion states, +3.4 pp in non-expansion states, DID +7.3 pp) and increased likelihood of hospitalizations (+9.9 pp in expansion states, -1.2 pp in non-expansion states, DID +11.1 pp) in Medicaid expansion compared with non-expansion states. There were no other significant differences in access, utilization or health trends between expansion and non-expansion states. After Medicaid expansion, low-SES adults age 55-64 were more likely to be hospitalized, suggesting poorer baseline access to chronic disease management and associated pent-up demand for health care services.